An expanded description of Blakea longiloba (Melastomataceae, Pyxidantheae) with notes on its distribution, conservation, and taxonomic affinities - Urrea, Johan; Iturralde, Gabriel A.; Baquero, Luis; Lapo-González, Nadia; Garzón-Suárez, Henry X.; Penneys, Darin S.; Jiménez, Marco M. (Phytotaxa, 2025)
Blakea longiloba has been known only from the southern region of Colombia. During botanical explorations in Ecuador, we have encountered more populations of this species which are reported here. The new records extend the known geographic range of B. longiloba by 500 km south of the previously documented southernmost locality. In addition, the new records help to improve the taxonomic circumscription of the species. We therefore provide an updated and expanded description, a Lankester Composite Digital Plate (LCDP), information on its ecology, phenology, etymology, distribution, conservation status, and taxonomic affinities.